PERANCANGAN PERPIPAAN DISTRIBUSI AIR BERSIH DUSUN BINA LOKA BLOK 6 MENGGUNAKAN PERANGKAT LUNAK EPANET 2.2 - mulyono, darajat; hery sonawan; Tohasan, Achmad (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
This study focuses on the design of a clean water distribution piping system for Bina loka Hamlet, Block 6, using EPANET 2.2 software. The research aims to address the challenges faced by the local community, including geographical constraints and varying water quality, by designing an efficient distribution system. The methodology involves collecting both primary and secondary data, including topographical surveys and water demand assessments. Using EPANET 2.2, the study simulates the hydraulic and water quality behaviors within the pipe network, optimizing the system for pressure and flow rates. The results indicate that the proposed design meets the necessary criteria for an effective water distribution system, ensuring adequate water supply and quality for the residents.